2004
DOI: 10.1021/ac0488762
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Identifiable Cross-Linking Strategy for Studying Protein−Protein Interactions

Abstract: A new mass spectrometry identifiable cross-linking strategy has been developed to study protein-protein interactions. The new cross-linker was designed to have two low-energy MS/MS-cleavable bonds in the spacer chain to provide three primary benefits: First, a reporter tag can be released from cross-link due to cleavage of the two labile bonds in the spacer chain. Second, a relatively simple MS/MS spectrum can be generated owing to favorable cleavage of labile bonds. And finally, the cross-linked peptide chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
260
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(269 citation statements)
references
References 27 publications
(32 reference statements)
6
260
0
3
Order By: Relevance
“…Steen et al exploited this low-energy fragmentation characteristic of mono-oxidized thio-ethers to profile phosphorylation by ␤-elimination and Michael addition chemical strategy [7]. It was reported that this characteristic neutral loss was generated by the formation of dehydroalanine in a cysteinyl residue after releasing a sulfenic acid fragment (RSOH, where R stands for added tag mass from the blocking reagent) from the modified peptide in a low-energy MS/MS experiment.This study was carried out to investigate new features for novel low-energy mass spectrometry cleavable cross linkers where bonds can be selectively dissociate with low-energy MS/MS in the gas-phase environment of a mass spectrometer [8,9]. Low-energy fragmentation characteristics of oxidized thio-ether bonds have been reported [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Steen et al exploited this low-energy fragmentation characteristic of mono-oxidized thio-ethers to profile phosphorylation by ␤-elimination and Michael addition chemical strategy [7]. It was reported that this characteristic neutral loss was generated by the formation of dehydroalanine in a cysteinyl residue after releasing a sulfenic acid fragment (RSOH, where R stands for added tag mass from the blocking reagent) from the modified peptide in a low-energy MS/MS experiment.This study was carried out to investigate new features for novel low-energy mass spectrometry cleavable cross linkers where bonds can be selectively dissociate with low-energy MS/MS in the gas-phase environment of a mass spectrometer [8,9]. Low-energy fragmentation characteristics of oxidized thio-ether bonds have been reported [6,7].…”
mentioning
confidence: 99%
“…This study was carried out to investigate new features for novel low-energy mass spectrometry cleavable cross linkers where bonds can be selectively dissociate with low-energy MS/MS in the gas-phase environment of a mass spectrometer [8,9]. Low-energy fragmentation characteristics of oxidized thio-ether bonds have been reported [6,7].…”
mentioning
confidence: 99%
“…One major shortcoming of chemical cross-linking approaches, however, is the tremendous sample complexity attributable to the wide variety of cross-linked products that can be created during the cross-linking reaction. To circumvent this disadvantage, a number of different strategies have been developed that have in common to facilitate identification of cross-linker containing species, e.g., by employing isotope-labeled cross-linkers [6,7], isotope-labeled proteins [8], cleavable cross-linkers [9], fluorogenic crosslinkers [10], or cross-linkers creating a characteristic marker ion during MS/MS analysis [11]. Another strategy to selectively enrich cross-linker containing species by using trifunctional cross-linkers containing a biotin moiety has been described recently [12][13][14].…”
mentioning
confidence: 99%
“…High  (Gruhler & Kratchmarova, 2008;Mann, 2006) 15 N-labeling High  Nelson et al, 2007) Chemical crosslinking-MS using protein interaction reporter (PIRs) Anderson et al, 2007;Tang et al, 2005) Protein microarrays High  (Angenendt et al, 2006;Popescu et al, 2007;Ramachandran et al, 2004) …”
Section: Stable-isotope Labeling Of Amino Acids In Cell Culture (Silac)mentioning
confidence: 99%